2018
DOI: 10.1038/s41419-017-0242-x
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy mediates glucose starvation-induced glioblastoma cell quiescence and chemoresistance through coordinating cell metabolism, cell cycle, and survival

Abstract: Metabolic reprogramming is pivotal to sustain cancer growth and progression. As such dietary restriction therapy represents a promising approach to starve and treat cancers. Nonetheless, tumors are dynamic and heterogeneous populations of cells with metabolic activities modulated by spatial and temporal contexts. Autophagy is a major pathway controlling cell metabolism. It can downregulate cell metabolism, leading to cancer cell quiescence, survival, and chemoresistance. To understand treatment dynamics and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 67 publications
0
32
1
Order By: Relevance
“…The elevated rates of glucose uptake and metabolism to sustain their rapid growth combined with nutrient deprivation in glioblastoma spheroids may cause autophagy enhancement and the transition of cells to a quiescent state (37) and promote survival, and as such constitutes a vital mechanism of drug resistance (38). Wang et al demonstrated that upon glucose starvation, while the majority of cancer cells perished due to chemotherapeutic cytotoxicity, subsets of cancer cells can up-regulate their autophagic activity, enter quiescence, and acquire survival advantage and ultimately chemoresistance (39).…”
Section: Discussionmentioning
confidence: 99%
“…The elevated rates of glucose uptake and metabolism to sustain their rapid growth combined with nutrient deprivation in glioblastoma spheroids may cause autophagy enhancement and the transition of cells to a quiescent state (37) and promote survival, and as such constitutes a vital mechanism of drug resistance (38). Wang et al demonstrated that upon glucose starvation, while the majority of cancer cells perished due to chemotherapeutic cytotoxicity, subsets of cancer cells can up-regulate their autophagic activity, enter quiescence, and acquire survival advantage and ultimately chemoresistance (39).…”
Section: Discussionmentioning
confidence: 99%
“…182 Several properties of CSC affect the impact of CQ on tumors. 184 These quiescent cells rely on autophagy. 183 During tumor growth, rapidly dividing cells that rely on glycolysis produce lactate.…”
Section: Cq Effects On Cancer Stem Cellsmentioning
confidence: 99%
“…This, in turn, generates an acidic microenvironment that when combined with hypoxia leads to the development of quiescent cancer cell clones that share properties with stem cells. 184 These quiescent cells rely on autophagy. 185 Through autophagy, cancer cells and especially cancer stem-like cell clones increase their capacity for material turnover and efflux of cancer drugs.…”
Section: Cq Effects On Cancer Stem Cellsmentioning
confidence: 99%
“…Glioblastoma (GBM) is the most malignant form of glioma and autophagy activation results in resistance to temozolomide [ 23 , 38 ], suggesting that autophagy targeting in combination with conventional therapy may have beneficial effects on therapy. A significant population of glioblastoma expresses a truncated EGFR receptor, epidermal growth factor receptor variant III (EGFRvIII), which is associated with increased hypoxia tolerance, radio- and chemoresistance and pro-survival [ 39 ].…”
Section: Brain Cancermentioning
confidence: 99%